Experimental demonstration of strain-based damage method for optimized fatigue testing of wind turbine blades. (1st August 2022) - Castro, Oscar; Yeniceli, Süleyman Cem; Berring, Peter; Semenov, Sergei; Branner, Kim
Abstract: A method for optimized testing of wind turbine blades under cyclic loading is experimentally demonstrated in this paper. The method uses continuous linear optimization to find the best combination of different uniaxial and multiaxial test blocks to achieve material-based damage targets across the blade and minimize test time. By applying the method on a real commercial wind turbine blade and comparing it with a standard fatigue test performed on a blade of the same type, the present work shows that improved fatigue tests can be obtained in terms of both accuracy and total test time.